OPINIONS OF MEDICAL FACULTY STUDENTS ON THE RATIONALITY OF USING TRADITIONAL MEDICINE FOR THE TREATMENT OF ONCOLOGICAL DISEASES - Kadirova G. B.; Akhmatov M. I.; Yakubova G.Q. (Journals Park Publishing, 2024)
During the training of students at the medical faculty, future doctors should develop professional thinking based on the principles of evidence-based medicine. To understand to what extent medical students are inclined to be guided by these principles when choosing treatment, a survey was conducted, including a question about the rationality of using various traditional medicine for the treatment of oncological diseases.
Keywords: Students, survey, evidence-based medicine, traditional medicine, oncological diseases.